Comparison of the Legal Regulation of Public Order in the Republic of Slovenia and the New Regulation in the Republic of Croatia - Tičar, Bojan (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
The legal regulation of misdemeanours against public order in the Republics of Slovenia and Croatia raises complex current and future legal and ethical dilemmas. Slovenian law is being amended, while the Republic of Croatia has taken and already adopted a new law that regulates several misdemeanours that the Slovenian legal system has not yet sanctioned. The paper focuses on similarities and differences between the systems using scientific research methods of teleological analysis of the current Slovenian constitutional system, grammatical interpretation of the current Slovenian and Croatian legislation, and comparative analysis of case studies. The new Slovenian law in this field will also consider the already adopted Croatian law and will undoubtedly have to intervene in the regulation of the introduction of modern technologies. Mobile applications will have to be designed and developed to facilitate reporting disturbances and violations of public order, as we live in a technological society.